High-Dose Steroid Treatment of Bacterial Keratitis. Issue 2 (February 2019) - Green, Matthew; Hughes, Ian; Hogden, John; Sara, Sergio; Apel, Andrew; Stapleton, Fiona
Abstract : Purpose: To describe the usage patterns of steroids in bacterial keratitis and to analyze the effect of steroids on patients' visual outcomes. Methods: This was a single-center retrospective review of patients with culture-positive bacterial keratitis treated between 1999 and 2015 at Princess Alexandra Hospital (Brisbane, Australia). Patients with culture-positive bacterial keratitis were identified through the Queensland Pathology Database, and clinical information was gathered through a subsequent medical record review. High-dose steroid treatment was classified as 6 or more drops of a steroid a day started within 7 days of corneal scraping. The outcome of a patient's episode of keratitis was classified as good if their final visual acuity was 6/12 or better; poor if it was 6/60 or worse or required a corneal transplant, otherwise it was classified as average. Microbiological and clinical variables' association with outcomes was evaluated in univariate analyses. Variables significant at P < 0.1 were examined in a multivariate ordinal logistic regression analysis created with forward variable selection with forced inclusion of steroid treatment (high, regular, low dose, and none). Results: A total of 328 patients were included from the 1002 reviewed charts. Of these patients, 164 (50.0%) were treated with steroids. Factors significantly associated with outcomes in the multivariate model were high-dose steroid treatment, visual acuity on presentation, age group, cause of keratitis, infiltrate size, and location. The odds ratio of better outcomes with high-dose steroids was 5.49 (confidence interval, 1.6–19.0, P = 0.007). Conclusions: High-dose steroid treatment is significantly associated with better visual outcomes in patients with culture-positive bacterial keratitis in this case series.